Piezoelectric strain control of terahertz spin current - Chaurasiya, Avinash (2023)
Electrical control of photogenerated terahertz (THz) spin current pulses from a spintronic emitter has been at the forefront for the development of scalable, cost-efficient, wideband optospintronic devices. Artificially combined ferroelectric and ferromagnet heterostructure provides the potential avenue to deterministically control the phase of THz spin current pulse through piezoelectric strain. Here, the electric field-mediated piezoelectric strain control of photogenerated THz spin current pulse from a multiferroic spintronic emitter is demonstrated. The phase reversal of the THz spin current pulse is obtained from the combined effect of piezoelectric strain and a small magnetic field applied opposite to the initial magnetization of the ferromagnet. The piezoelectric strain-controlled phase switching of THz spin current thus opens a door to develop efficient strain engineered scalable on-chip THz spintronics devices.